Gender and Right-Wing Authoritarianism in a working-class case-study - Lundskow, George; Phillips, Brian; Curtiss, Phyllis (Journal of Public Governance, 2019)
Objective: In this article we attempt to shed light on the changing attitudes American workers may have, specifically authoritarian personality characteristics, by reviewing the results obtained from our survey of 74 retired auto workers.Research Design & Methods: Part of our survey utilizes the Zakrisson short version of the Right-Wing Authoritarian scale and our interests are to provide any differences found between men and women. Also, we seek to test for the presence of authoritarianism as one aspect to understand the appeal of right-wing politics among the white working class.Findings: Our findings indicate that men and women are each no more or less likely to develop authoritarian personality characteristics. The differences by gender that we found in our case-study mirror the literature over the last several decades since empirical research began in 1950 – ambivalence.Implications/Recommendations: As a discontented citizenry searches for answers, by leaning more politically right or left will gender differences widen or converge due to the issues.Contribution/Value Added: Given the current social and economic climate in the United States we find this research study to be both timely and important. A conservative or liberal orientation by American workers may have important contributions for the direction the US takes not only on pressing economic and social issues at home but abroad as well.